Retrospective analysis and current state of the improving qualification of pharmacists on quality questions of medicines in Shupyk NMAPE - S. H. Ubohov; L. B. Pilipchuk; V. I. Todorova; A. P. Radchenko; L. O. Fedorova; T. M. Budnikova; O. Yu. Kvitnytska (The State Expert Center of the Ministry of Health of Ukraine, 2019)
To date, one of the advanced educational and research centers of Kiev and Ukraine, which is the improving qualification of pharmacists on quality questions of medicines, is the Department of Quality Control and Standardization of Medicines of Shupyk National Medical Academy of Post-Graduate Education (NMAPE). The aim of the work is to analyze the historical stages of formation and development of the Department of Quality Control and Standardization of Medicines of Shupyk NMAPE. The materials of the research are: archival and current documentation of the department, scientific publications, encyclopedic reference materials. Studies were conducted using methods: content analysis, historical documentary, generalization and systematization of historical data. In this work a retrospective analysis was performed and current state of activity of the Department of Quality Control and Standardization of Medicines of Shupyk NMAPE was considered. The basic stages of formation and historical development of the department during 1938 to 2018 are determined. The contribution to the development of pharmaceutical education and science of professors (prof. Ya.A. Fialkov, N.P. Maksyutina, O.M Gritsenko, N.O. Vetiutneva, etc.) was noted. The educational cycles, taught at the department, are shown, namely: specialization cycles, internships, pre-certification training in the specialties «Analytical Control Pharmacy», «General Pharmacy»; thematic improvement cycles on topical issues of pharmacy, quality assurance and prevention of falsification of medicines, functioning of quality systems of pharmacies (for pharmacists); cycles of improvement of assistant pharmacists; thematic improvement cycles on the scientific basis of phytotherapy and the use of modern medicines based on active ingredients of natural origin (for physicians). The basis of educational-methodical and scientific production of the department is described. The main areas of the scientific activity of the department are described, covering the following areas: development of methods for the investigation of complex synthetic compounds, methods for express analysis of extemporal multicomponent medicines, methods for quality control the of phytotherapeutic and homeopathic medicines; study of the composition and intermolecular interaction of biologically active compounds in plants and phytopreparations; synthesis and creation of new medicines and dietary supplements; study of the properties of crown compounds; study of the interaction of auxiliary substances with active ingredients; research on increasing the solubility of difficult soluble substances; substantiation of methodological and organizational-methodical principles of quality assurance of medicines at stages of wholesale, retail sale and medical use, etc. Analysis of the activities of the Department of Quality Control and Standardization of Medicines of Shupyk NMAPE during 1938 to 2018 testifies to its significant contribution and great potential for the development of pharmaceutical science and practice, in particular in the direction of the creation, standardization, assurance and control of quality of medicines and dietary supplements.